Playing by the rules. The Hague courts and the Acteonisation du Grand Veneur d’Hollande (1643) - Keblusek, Marika (De Zeventiende Eeuw: Cultuur in de Nederlanden in interdisciplinair perspectief, 2017)
This article discusses an unpublished play, Acteonisation du Grand Veneur d’Hollande (1643). Created – and possibly performed – within the immediate circle of the court of Elizabeth of Bohemia in The Hague, its anonymous author satirizes the various personalities in the Orange courts of respectively Frederik Hendrik and Amalia von Solms, and Willem ii and Mary Stuart. Focusing on the social ambitions of Johannes Polyander van Kerckhoven, Lord of Heenvliet, and by using the popular myth of Actaeon and Diana, the clash between court and city, between princely aristocrats and republican burghers is played out.